KAJIAN MACAM MULSA TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS KEDELAI (Glycine max (L.) Merrill) - Priyono, Iksan; Santosa, Sartono Joko; Sumarmi, Sumarmi (Innofarm:Jurnal Inovasi Pertanian, 2021)
The study of mulch on the growth and yield of three varieties of Soybean (Glycine Max (L.) Merrill) "has been conducted from October 9, 2020 to January 4, 2021 in Donohudan Village, Ngemplak, Boyolali. This study aims to examine the types of mulch on the growth and yield of three soybean varieties (Glycine max (L.) Merrill). In this study using a Randomized Complete Block Design (RCBD) arranged in a Split Plot consisting of 2 treatment factors, namely the variety of soybeans as the main plot (main plot) and the kinds of mulch as the sub plot (subplots), so that 9 combinations of treatments and each repeated 3 times. Data were analyzed using Variance Analysis and followed by Honest Real Difference Test at the 5% level. The results showed that the mulch treatment had no significant effect on plant height and number of leaves. However, it has the best plant height in the treatment without using mulch (M1) with 94.63 cm and the best number of leaves is 31 leaves. Silver black plastic mulch (M2) treatment significantly affected the weight of wet stover with 203.33 grams and dry weight of stover with 90.25 grams, pod weight with 236.02 grams, number of seeds with 224 grains, and seed weight with 46 grams. Treatment of various varieties did not significantly affect the number of pods, pod weight, and weight of 100 soybeans. However, it had the best number of pods in the Anjasmoro variety (V1) with 133 pods, the best pod weight was in the Biosoy variety (V3) with 202.59 grams, and the best weight of 100 soybeans was in the Grobogan (V2) variety with 26.50 grams. Treatment of varieties in Anjasmoro (V1) variety significantly affected the number of seeds with 230 grains, Biosoy (V3) variety had a significant effect on the weight of seeds with the best weight of 40.48 grams.